An unexpected encounter with jejunal web after foreign bodies entrapment in a toddler - Yik, Yee Ian; How, Ann Kee (Malaysian Medical Association, 2019)
We present a very rare case of jejunal web discovered after a toddler presented with foreign bodies entrapment, following incidental ingestion. This is perhaps the first case reported in the English publication. Expectant management with spontaneous passage of foreign bodies failed. Serial abdominal radiographs failed to determine the site of the foreign bodies accurately. Endoscopic removal was unsuccessful. Surgical removal was warranted with unexpected intra-operative finding of a jejunal web with foreign body entrapment. Although rare, a congenital intestinal web must be considered in a child presents with failure of expectant management following foreign body ingestion as surgical intervention is necessary.